2013
DOI: 10.1186/1745-6673-8-25
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a medical hypnotherapy on clothing industry employees suffering from chronic pain

Abstract: BackgroundProblems associated with pain in several body regions due to work-related musculoskeletal disorders (WRMDs), repetitive movement and negative stress at work are quite common in many manufacturing industries of Latvia, int.al. clothing industry. The aim of this study was to evaluate efficiency of the psychotherapeutic intervention using medical hypnotherapy (MH) program for mind-body relaxation with pain-blocking imagery, cognitive restructuring of unpleasant physical and emotional experience.Methods3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(28 reference statements)
2
5
0
Order By: Relevance
“…We have shown a decrease in pain interference in daily life for the self‐hypnosis/self‐care group. These results are consistent with studies showing decreases of pain interference in patients with chronic musculoskeletal pain (Tan et al., ; Roja et al., ). Catastrophizing involves a tendency to focus on pain and to evaluate its effects in unrealistic and overly negative terms (Jensen et al., ) and was associated with pain interference in chronic pain patients (Keefe et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have shown a decrease in pain interference in daily life for the self‐hypnosis/self‐care group. These results are consistent with studies showing decreases of pain interference in patients with chronic musculoskeletal pain (Tan et al., ; Roja et al., ). Catastrophizing involves a tendency to focus on pain and to evaluate its effects in unrealistic and overly negative terms (Jensen et al., ) and was associated with pain interference in chronic pain patients (Keefe et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…By highlighting the quality of life improvement in the self‐hypnosis/self‐care group, our results support studies involving musculoskeletal disorders (Roja et al., ), irritable bowel syndrome (Bremner, ) and Parkinson disease (Elkins et al., ). Our results fit with a review showing the effectiveness of cognitive behavioural treatment in improving quality of life, as indexed by positive changes in disability, psychological distress and pain in chronic pain patients (Eccleston et al., ).…”
Section: Discussionsupporting
confidence: 86%
“…Several scales and instruments have been developed based on this methodology, e.g., World Health Organization Disability Assessment Schedule (WHODAS) [63], World Health Organization Quality of Life (WHOQOL-BREF) [64] and RAND-36 [65]. These ask questions about the ability of individuals to undertake tasks of daily living [66]. These instruments have also been applied to mental, neurological, and addictive disorders [67].…”
Section: Risk Management In Health and Safetymentioning
confidence: 99%
“…The results showed that the low muscle resistance is related to pain. Roja et al [139] evaluated the effectiveness of psychotherapeutic intervention with medical hypnotherapy in workers with chronic pain in the textile industries of Latvia. The results show that this is an effective method to diminish the intensity of muscle pain and fatigue.…”
Section: Manufacturing Industry For Textiles and Footwearmentioning
confidence: 99%